2020
DOI: 10.18632/aging.103306
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B improves cognitive impairment by inhibiting neuroinflammation and decreasing Aβ level in Porphyromonas gingivalis-infected mice

Abstract: Amyloid-β (Aβ) accumulation is one of the main pathological hallmarks of Alzheimer’s disease (AD). Porphyromonas gingivalis ( P. gingivalis ), the pathogen of chronic periodontitis, could cause Aβ accumulation and was identified in the brain of AD patients. Salvianolic Acid B (SalB) has been proven to have the neuroprotective effect. Whether SalB could protect against P. gingivalis -induced cognitive impairment is still unknown. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…The bidirectional interaction between Aβ deposition and neuroinflammation resulted in the apoptosis of neurocytes and then impaired cognitive function in the Pg group. It is reported that inhibition of Pg-induced neuroinflammation can decrease the deposition of Aβ ( Dominy et al., 2019 ; Liu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional interaction between Aβ deposition and neuroinflammation resulted in the apoptosis of neurocytes and then impaired cognitive function in the Pg group. It is reported that inhibition of Pg-induced neuroinflammation can decrease the deposition of Aβ ( Dominy et al., 2019 ; Liu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, chronic P gingivalis or P gingivalis LPS administration increased the number of activated microglial cells and astrocytes in the cortex 148,153 and in the hippocampus 143,145,150,152,154 as an indicator of the local inflammation. Pro‐inflammatory mediators, like IL‐1β, IL‐6, TNFα, INF‐γ, were elevated compared to controls on mRNA and protein level 143,144,146‐150,152‐154 …”
Section: Porphyromonas Gingivalis – Animal and In Vitro‐studiesmentioning
confidence: 99%
“…Proinflammatory mediators, like IL-1β, IL-6, TNFα, INFγ, were elevated compared to controls on mRNA and protein level. 143,144,[146][147][148][149][150][152][153][154] In terms of the β amyloid deposition, precursor proteins (APP)…”
Section: Animal Studiesmentioning
confidence: 99%
“…Ragarding its effects on the skeletal system, salvianolic acid B promotes new bone formation and protects against oxidative damage (Kayalar et al 2020 ; Xiao et al 2020 ; Bian and Xiang 2020 ); it improves atherosclerosis by inhibiting the YAP/TAZ/JNK signaling pathway in endothelial cells and pericytes (Yang et al 2020 ). In the nervous system, salvianolic acid B could improve the cognitive impairment of mice infected with Porphyromonas gingivalis by inhibiting neuroinflammation and reducing Aβ level (Liu et al 2020 ). Salvianolic acid B can also improve chronic mild stress-induced depressive behaviors in rats via the AMPK/SIRT1 signaling pathway (Liao et al 2020 ).…”
Section: Trpcs Antagonistsmentioning
confidence: 99%